Bond behavior of spirally confined splice of deformed bars in grout. (1st April 2015) - Hosseini, Seyed Jamal Aldin; Rahman, Ahmad Baharuddin Abd.; Osman, Mohd Hanim; Saim, Aziz; Adnan, Azlan
Highlights: A spiral combined with splice bars as an alternative grouted connection. Significant increase in bond strength for rebars connected by the spiral connection. More effective confinement and higher bond strength with smaller spiral diameters. Similar trends of bond behavior observed in axial and flexural pull-out tests. Lower bond strength in flexural specimens compared to axial pull-out specimens. Abstract: This paper presents the bond behavior of deformed steel reinforcement bars connected by a grouted spiral connection. The bond behavior investigated in this study comprised the mechanism of force transfer, the bond-slip relationship due to the effects of spiral diameter and the comparison of bond stresses between axial and flexural pull-out tests. A total of 36 pull-out specimens and 12 beam specimens were tested until bond failure. The results show that the bond performance between rebars and grout improved significantly due to the confinement provided by the spiral. Reducing the spiral diameter increases the confinement effect and subsequently increases the bond strength. The results also show that the bond strengths obtained from the flexural tests are within the range of 0.74–0.79 times the bond strength of the axial pull-out tests. However, both test results show similar trend of bond behavior with respect to variation in spiral configurations.